A flexible surface-enhanced raman substrate and a method of making the same
Patent Information
- Application Number
- CN202410573984.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-10
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-05-10
AI Technical Summary
[0003]然而,这些方法在增强效果、再现性和规模化生产方面都面临一些挑战
[0021] (1) The flexible surface-enhanced Raman substrate provided by the present invention has metal nano gaps arranged in an array on the substrate surface and are small enough. Due to the small size of the nano gaps in the metal nanostructure, the local electromagnetic field effect is strong enough, and the substrate has excellent detection sensitivity.
Smart Images

Figure CN118603956B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of trace substance detection and relates to a flexible surface-enhanced Raman substrate and its preparation method. Background Technology
[0002] After decades of development, surface-enhanced Raman spectroscopy (SERS) detection technology has been widely applied in various fields such as biomedicine, food safety, and drug detection, becoming an important tool for trace substance detection. Its enhancement principle is based on the resonant excitation of the surface plasmon effect of metal nanostructures, thereby forming a locally enhanced electromagnetic field on the surface of the metal nanostructure. This significantly enhances the Raman signal of the analyte located near the enhanced electromagnetic field. Common metal nanoparticle surfaces and metal structure arrays containing extremely small nano-gap (typically less than 10 nanometers) can both produce local electromagnetic field enhancement effects. The enhancement magnitude is inversely proportional to the nano-gap size; that is, the smaller the gap, the stronger the enhancement effect. To make SERS a routine and online analytical detection tool, the most important thing is to develop effective enhancement substrates based on metal structures, while possessing high signal enhancement capability, good reproducibility, and low manufacturing cost. Currently, commonly used methods for preparing SERS substrates mainly include colloidal nanoparticle self-assembly / solution, electrochemical deposition, template methods, and micro / nano fabrication techniques such as photolithography (e.g., laser direct writing, electron beam / ion beam lithography).
[0003] However, these methods face challenges in terms of enhancement, reproducibility, and large-scale production. For example, while SERS substrates prepared by the self-assembly of noble metal nanoparticles exhibit high detection sensitivity, their reproducibility is poor, and the resulting structures are not uniform enough, hindering large-scale manufacturing. On the other hand, micro / nano-based fabrication methods, while achieving better structural control and sub-10 nanometer gap structures, suffer from drawbacks such as low processing efficiency and high manufacturing costs.
[0004] For the reasons mentioned above, there is an urgent need to study a surface-enhanced Raman substrate with high fabrication efficiency and excellent structure. Summary of the Invention
[0005] To overcome the aforementioned problems, the inventors conducted intensive research and developed a flexible surface-enhanced Raman spectroscopy (SERS) substrate and its preparation method. The substrate surface contains an array of metal nano-gap structures with a width of 3–5 nm. Due to the sufficiently small width of these metal nano-gap structures, the generated localized electromagnetic field effect is sufficiently strong, resulting in excellent detection sensitivity. The substrate preparation method is very simple, involving the deposition of metal and molecular self-assembly, followed by exfoliation and transfer. It exhibits excellent reproducibility in SERS studies, thus completing this invention.
[0006] Specifically, the object of the present invention is to provide the following aspects:
[0007] In a first aspect, a flexible surface-enhanced Raman spectroscopy substrate is provided, wherein the substrate surface contains an array of metal nano-gap 21, the width of which is 3 to 5 nm.
[0008] Optionally, the substrate is based on a flexible organic material.
[0009] Optionally, a metal layer is attached to the surface of the substrate.
[0010] Optionally, the metal layer comprises an array of metal nanostructures.
[0011] Optionally, the metal nanostructure is separated from the metal layer by a self-assembled monolayer.
[0012] In a second aspect, a method for preparing the substrate described in the first aspect is provided, the method comprising:
[0013] Step 1: Deposit metal on the substrate surface in one step and self-assemble it to obtain the first composite layer;
[0014] Step 2: Deposit metal a second time on the first composite layer to obtain the second composite layer;
[0015] Step 3: Transfer the deposited metal and self-assembled structure to the surface of a flexible organic material to obtain the substrate.
[0016] In step 1, the substrate is preferably a silicon wafer or quartz glass.
[0017] In step 1, the metal is a precious metal, preferably selected from gold, silver, platinum or palladium.
[0018] In step 3, the flexible organic material is a polymer or organosilicon.
[0019] Thirdly, the application of the substrate described in the first aspect or the substrate prepared according to the method described in the second aspect in Raman spectroscopy detection is provided.
[0020] The beneficial effects of this invention include:
[0021] (1) The flexible surface-enhanced Raman substrate provided by the present invention has metal nano gaps arranged in an array on the substrate surface and are small enough. Due to the small size of the nano gaps in the metal nanostructure, the local electromagnetic field effect is strong enough, and the substrate has excellent detection sensitivity.
[0022] (2) The flexible surface-enhanced Raman substrate provided by this invention can achieve a detection limit as low as 10 for the concentration of samples such as Rhodamine 6G. -12 ~10 -16 M.
[0023] (3) The flexible surface-enhanced Raman substrate provided by the present invention is flexible, so it can be closely attached to the surface of the non-planar test object. Furthermore, due to its high transparency, both the detection laser and the Raman scattered light can pass through smoothly, thereby realizing in-situ Raman detection of trace substances on non-planar surfaces.
[0024] (4) The method for preparing the flexible surface-enhanced Raman substrate provided by the present invention is very simple, and the gap size is precisely controllable. The substrate has excellent performance and excellent repeatability in surface-enhanced Raman scattering spectroscopy studies. Attached Figure Description
[0025] Various other advantages and benefits of the present invention will become apparent to those skilled in the art upon reading the detailed description of the preferred embodiments below. The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. It is obvious that the drawings described below are merely some embodiments of the invention, and those skilled in the art can obtain other drawings based on these drawings without any inventive effort.
[0026] In the attached diagram:
[0027] Figure 1(a) shows a schematic diagram of the metal deposition and heat treatment on the substrate surface during substrate preparation;
[0028] Figure 1(b) shows a schematic diagram of a substrate containing a self-assembled monolayer obtained during substrate preparation;
[0029] Figure 1(c) shows a schematic diagram of secondary metal deposition during substrate preparation;
[0030] Figure 1(d) shows a schematic diagram of coating a flexible organic material onto the surface of a metal layer during substrate fabrication;
[0031] Figure 1(e) shows a schematic diagram of peeling a flexible organic material with a deposited metal layer and a self-assembled monolayer from a substrate during substrate fabrication.
[0032] Figure 1(f) shows a schematic diagram of the substrate structure prepared according to the preferred embodiment;
[0033] Figure 2(a) shows a macroscopic image of the substrate prepared in Example 1;
[0034] Figure 2(b) shows a macroscopic image of the substrate prepared in Example 1 rolled up;
[0035] Figure 3 The surface SEM characterization of the substrate prepared in Example 1 is shown;
[0036] Figure 4 This shows a surface atomic force micrograph of the substrate prepared in Example 1;
[0037] Figure 5 Show Figure 4 Nanoscale gap size profile of the white line in the middle;
[0038] Figure 6 The comparison diagram of Raman spectroscopy tests in Example 1 is shown;
[0039] Figure Labels
[0040] 1-Metal nanostructure layer;
[0041] 2-Self-assembled monolayer;
[0042] 21-Metallic nano-interstic gaps;
[0043] 3-Base;
[0044] 4-Metallic layer;
[0045] 5-Substrate. Detailed Implementation
[0046] The following will refer to the appendix. Figures 1(a) to 6 Specific embodiments of the invention will be described in more detail below. While specific embodiments of the invention are shown in the accompanying drawings, it should be understood that the invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to enable a more thorough understanding of the invention and to fully convey the scope of the invention to those skilled in the art.
[0047] It should be noted that certain terms are used in the specification and claims to refer to specific components. Those skilled in the art will understand that different terms may be used to refer to the same component. This specification and claims do not distinguish components based on differences in terminology, but rather on differences in function. The terms "comprising" or "including" used throughout the specification and claims are open-ended and should be interpreted as "comprising but not limited to." The following descriptions are preferred embodiments for carrying out the invention; however, these descriptions are for the purpose of understanding the general principles of the specification and are not intended to limit the scope of the invention. The scope of protection of this invention is determined by the appended claims.
[0048] In the description of this invention, it should be noted that the terms "upper," "lower," "inner," "outer," "front," and "rear," etc., indicate the orientation or positional relationship based on the orientation or positional relationship in the working state of this invention, and are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this invention. Furthermore, the terms "first," "second," "third," and "fourth" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.
[0049] To facilitate understanding of the embodiments of the present invention, further explanations and descriptions will be provided below with reference to the accompanying drawings and specific embodiments. The accompanying drawings do not constitute a limitation on the embodiments of the present invention.
[0050] On one hand, according to the present invention, a flexible surface-enhanced Raman substrate is provided, wherein the substrate surface contains an array of metal nano-gap 21, the width of which is 3 to 5 nm.
[0051] In particular, since the width of the metal nano-gap 21 is small enough, the local electromagnetic field effect is strong enough, and the substrate has excellent detection sensitivity.
[0052] In this invention, the substrate can achieve a detection limit as low as 10 for the concentration of samples such as rhodamine 6G. -12 ~10 -16 M (mol / L).
[0053] According to a preferred embodiment, as shown in FIG1(f), the substrate is based on a flexible organic material as a base 3, and a metal layer 4 is attached to the surface of the base 3. The metal layer 4 includes an array of metal nanostructure layers 1, which are separated from the metal layer 4 by self-assembled monolayers 2. The metal nanostructure layers 1 are arrayed on the surface of the metal layer 4, and the self-assembled monolayers 2 form metal nano gaps 21 on the surface of the metal layer 4.
[0054] Furthermore, the metal layer 4 is preferably made of the same material as the metal nanostructure layer 1 to improve the compatibility between the materials. It is preferably a precious metal, selected from gold, silver, platinum or palladium, and more preferably gold or silver, such as gold.
[0055] Among them, the precious metals have high reflectivity, low electrochemical corrosion and good electrical conductivity, but gold and silver have unique advantages in price.
[0056] According to the present invention, the width of the metal nanogap 21 is approximately equal to the length of the self-assembled monomolecule forming the self-assembled monolayer 2, which is approximately 3 to 5 nm.
[0057] According to the present invention, the thickness of the substrate 3 is required to ensure good flexibility. The thickness of the substrate 3 is 2 to 100 μm, preferably 5 to 50 μm, more preferably 10 to 30 μm, for example 20 μm.
[0058] Furthermore, in order to ensure that the substrate has a certain degree of transparency, the thickness of the metal layer 4 cannot be too thick. Preferably, the thickness of the metal layer 4 is 10-60 nm, more preferably 12-50 nm, and even more preferably 15-25 nm, for example 15 nm.
[0059] On the other hand, according to the substrate preparation method described in the first aspect of the present invention, such as Figures 1(a) to 1(f) As shown, the method includes:
[0060] Step 1: Deposit metal on the surface of substrate 5 in one step and self-assemble it to obtain the first composite layer;
[0061] Step 2: Deposit metal a second time on the first composite layer to obtain the second composite layer;
[0062] Step 3: Transfer the deposited metal and self-assembled structure to the surface of a flexible organic material to obtain the substrate.
[0063] The preparation method of the substrate is described in detail below.
[0064] In step 1, as Figures 1(a) to 1(b) As shown, the substrate 5 serves as the base material for metal deposition. During self-assembly, the self-assembled monomolecules form chemical bonds with the metal, thereby forming a self-assembled monolayer 2 on the metal surface. This provides a surface with specific structure and properties for the subsequent second composite layer, thus affecting the final substrate performance. Alternatively, it can be said that after self-assembly, a self-assembled monolayer 2 is formed on the surface of the first-deposited metal.
[0065] In step 1, the substrate 5 is not strictly limited, but is preferably a silicon wafer or quartz glass, typically 2 inches or 4 inches in size. The substrate 5 needs to have high flatness, uniformity, and heat resistance. Silicon wafers and quartz glass have high surface flatness and uniformity, which helps the metal form a uniform and flat nanostructure on its surface. Both silicon wafers and quartz glass can withstand high-temperature processing, which is beneficial for preventing deformation during subsequent heat treatment. Furthermore, both silicon wafers and quartz glass have good chemical stability, resisting chemical reactions and maintaining their surface properties, thereby ensuring the stability and controllability of the self-assembly process.
[0066] In step 1, the thickness of the deposited metal is 2 to 10 nm, preferably 3 to 9 nm, more preferably 6 to 8 nm, for example 8 nm.
[0067] In step 1, the metal deposited in the first step is processed through steps 2 and 3 to form a metal nanostructure layer 1. For ease of description, Figures 1(a) to 1(f) All are shown as metal nanostructure layer 1.
[0068] The thickness of the metal nanostructure layer 1 needs to be in the range of 2 to 10 nm to ensure that different nanostructures can be formed after heat treatment. If the thickness is too low, the size of the metal nanoparticles formed may be too small, affecting the success rate or stability of subsequent structure transfer. If the thickness is too high, it will lead to the formation of a continuous and dense metal film, and heat treatment will not be able to form a metal nanostructure, thus maintaining the morphology of the metal film.
[0069] In step 1, the metal is a precious metal selected from gold, silver, platinum or palladium, preferably gold or silver, and most preferably gold.
[0070] Furthermore, noble metals such as gold and silver can generate strong plasmon resonance effects on their surfaces, thereby significantly enhancing the local electromagnetic field. This enhancement is highly valuable for various nanophotonics and biosensing applications. Fourth, gold and silver are relatively chemically stable and resistant to oxidation, allowing them to maintain their performance under various environmental conditions. Fifth, gold and silver are readily available for fabricating desired metallic structure arrays.
[0071] In step 1, a vacuum deposition method is preferred for depositing metal on the surface of substrate 5 in a single step. Vacuum deposition allows for precise control of the metal deposition thickness, which is crucial for preparing a second composite layer with a specific microstructure. Furthermore, vacuum deposition is performed in a high-vacuum environment, reducing interference from airborne impurities and resulting in a high-purity metal film.
[0072] Preferably, during vacuum coating, the vacuum level is controlled to be 10. -4 ~10 -8 mbar, preferably 10 -6 ~10 -8mbar, for example, 10 -7 mbar is used to achieve high uniformity in vacuum coating.
[0073] In step 1, preferably, the substrate 5 after the first deposition is heat-treated at 150-250°C for 0.5-3 hours, more preferably, the substrate 5 after the first deposition is heat-treated at 180-210°C for 1-2 hours, for example, the substrate 5 after the first deposition is heat-treated at 200°C for 1 hour.
[0074] Among them, heat treatment is beneficial to improve the adhesion between the metal and the substrate 5, and can also form different morphologies of metal nanostructures 1 according to the thickness of the deposited metal.
[0075] In step 1, the self-assembly includes: placing the substrate 5 obtained by a single metal deposition in a self-assembly molecular solution to form a self-assembled monolayer 2 on the metal surface, followed by cleaning and drying to obtain a first composite layer.
[0076] Furthermore, the self-assembled molecular solution is preferably an octadecyl mercaptan-isopropanol solution and / or an octadecyl mercaptan-ethanol solution, more preferably an octadecyl mercaptan-ethanol solution.
[0077] In this process, the sulfur atoms in the self-assembled monomolecule of n-octadecyl thiol form a strong chemisorption with the surface of metals such as gold. This indicates a highly stable bond between the sulfur atoms and metal atoms, allowing for the formation of a uniform molecular layer on the deposited metal surface. Furthermore, the thiol head of the thiol molecule is adsorbed onto the deposited metal surface, while the carbon chain tail at the other end faces outwards, forming a monolayer. Metals, particularly gold, have low surface energy, making it easier for thiol molecules to form stable self-assembled monolayers on their surfaces. The surface structure of gold also facilitates the formation of a highly ordered structure of thiol molecules on the gold surface.
[0078] According to the present invention, the length of the self-assembled monomolecules in the self-assembled molecular solution is 2 to 5 nm, preferably 3 to 5 nm, for example 3 nm. The nano-gap width determined by the self-assembled monomolecules of this length can generate a strong local electromagnetic field effect.
[0079] According to the present invention, during the heat treatment process, the dewetting properties of the deposited metal cause it to form a metal nanostructure layer 1 on the substrate surface. Furthermore, since the substrate 5 is chemically inert, no chemical reaction occurs between it and the self-assembled monomolecules. The areas of the substrate 5 where no metal is deposited are filled with metal during subsequent secondary deposition, thereby forming an array of metal nano-gap spaces 21 at the junction with the substrate 5. When transferred to the surface of a flexible organic material, it presents as a substrate containing the array of metal nano-gap spaces 21.
[0080] According to the present invention, the concentration of self-assembled monomolecules in the self-assembled molecule solution is 2 to 5 mmol, preferably 2 to 4 mmol, for example 3 mmol.
[0081] In step 1, during self-assembly, the settling time is 4 to 8 hours, preferably 4 to 6 hours, for example 5 hours.
[0082] The settling time during the self-assembly process is crucial for the formation of a uniform, ordered, and stable self-assembled monolayer 2. Since the self-assembled monomolecules interact with the metal to form a stable self-assembled monolayer 2, if the settling time is too short, a dense self-assembled monolayer 2 cannot be formed on the metal surface; if the settling time is too long, it is not practically meaningful. Typically, a settling time of 4–8 hours is sufficient to form a dense and stable self-assembled monolayer 2 on the metal surface.
[0083] In step 1, after self-assembly, the cleaning is preferably done with inexpensive and readily available ethanol, which is used to clean excess self-assembled monomolecules; the drying is preferably done by blowing nitrogen gas onto the substrate 5.
[0084] In step 2, as shown in Figure 1(c), after a second metal deposition on the surface of substrate 5, the resulting metal layer 4 has a thickness of 10-60 nm, preferably 12-50 nm, more preferably 15-25 nm, for example 15 nm.
[0085] In step 2, the deposited metal material is preferably the same as the metal material deposited in step 1, for example, both are gold or silver, and more preferably both are gold.
[0086] In step 2, a secondary metal deposition is preferably performed using vacuum deposition. More preferably, the vacuum deposition parameters are consistent with those used in step 1 to improve the quality of the substrate. For example, the vacuum level is controlled to be 10. -4 ~10 -8 mbar, preferably 10 -6 ~10 -8 mbar such as 10 -7 mbar.
[0087] In step 3, as Figure 1(d) and 1(f) As shown, a flexible organic material is coated on the second composite layer. After curing, the flexible organic material with the deposited metal layer 4 and self-assembled monolayer 2 is peeled off from the substrate 5, thereby transferring the metal and self-assembled structure deposited on the second composite layer to the surface of the flexible organic material.
[0088] Furthermore, the flexible organic material serves as the substrate 3 and also as the support layer of the substrate. The flexible organic material can be a polymer such as poly(dimethyl terephthalate) (PET), polyamide (PI), polyurethane (PU), etc., or it can be an organosilicon such as polysiloxane (PDMS), etc., preferably an organosilicon, more preferably polysiloxane (PDMS).
[0089] Polysiloxanes possess excellent flexibility and ductility, allowing for significant deformation without breakage. They also exhibit strong resistance to most chemical substances, remaining unaffected by solvents, acids, alkalis, and oxygen, making them highly stable in chemical environments. Furthermore, due to their high transparency in the visible light range, detection can be performed using both front and back light irradiation.
[0090] In step 3, the thickness of the flexible organic material is 2 to 100 μm, preferably 5 to 50 μm, more preferably 10 to 30 μm, for example 20 μm.
[0091] In step 3, the curing temperature is 50–120°C, preferably 60–100°C, for example 60°C.
[0092] In step 3, the curing time is 30 to 120 minutes, preferably 40 to 100 minutes, for example 60 minutes.
[0093] The curing temperature and time have a significant impact on the substrate's performance. Curing temperature and time affect the crosslinking density, i.e., the number of crosslinking points in the flexible organic material network. Higher temperatures and longer times generally lead to higher crosslinking densities, resulting in a tighter network that is less likely to bond with the deposited metal layer 4. Appropriate curing temperature and time ensure the integrity of the flexible organic material structure, avoiding defects such as bubbles and cracks. Furthermore, it ensures the mechanical properties, chemical stability, and permeability of the resulting substrate. Within the aforementioned curing temperature and time range, ideal substrates can be fabricated.
[0094] Thirdly, the application of the substrate described in the first aspect or the substrate prepared by the method described in the second aspect according to the present invention in Raman spectroscopy detection.
[0095] The present invention is further described below through specific examples; however, these examples are merely exemplary and do not constitute any limitation on the scope of protection of the present invention.
[0096] Example 1
[0097] Prepare the cleaned 4-inch silicon wafers at 10 -7Gold was deposited once on the surface of a silicon wafer under a vacuum of mbar. The thickness of the gold-covered area was measured to be 8 nm. Then, the gold-deposited substrate 5 was heat-treated at 200°C for 1 h and cooled to room temperature. Next, it was placed in an octadecyl mercaptan-ethanol solution (octadecyl mercaptan concentration of 3 mmol, octadecyl mercaptan molecule length of about 3 nm) and left to stand for 5 h to form an octadecyl mercaptan monolayer on the gold surface. After standing, the substrate was removed and excess octadecyl mercaptan molecules were washed off with ethanol solution. The substrate 5 was then dried with nitrogen to obtain the first composite layer.
[0098] The first composite layer is applied again at 10. -7 Gold was deposited twice under a vacuum of mbar. After removal, a second composite layer was obtained. The thickness of the metal layer 4 was measured to be 15nm, with the surface of substrate 5 as the base surface.
[0099] Polysiloxane was coated on the second composite layer and cured at 60°C for 60 min, with the cured polysiloxane having a thickness of 20 μm. The polysiloxane containing the gold and n-octadecyl mercaptan monolayer was peeled off from the silicon wafer to obtain a flexible surface-enhanced Raman substrate.
[0100] Figure 2(a) shows a macroscopic image of the fabricated substrate, and Figure 2(b) shows a macroscopic image of the fabricated substrate rolled up. Combining Figure 2(a) and Figure 2(b), it can be seen that the substrate has good flexibility and can be fabricated over a large area. Figure 3 The surface SEM image of the fabricated substrate is shown. Figure 4 This shows a surface atomic force micrograph of the fabricated substrate, combined with... Figure 3 and Figure 4 It can be seen that the metal nano-interstices on the substrate surface are arranged in an array; Figure 5 Show Figure 4 The outline of the nanometer gap size shown in the white line indicates that it is approximately 5 nm.
[0101] Rhodamine 6G was diluted with water to obtain concentrations of 10. -14 M, 10 -12 M, 10 -10 M, 10 -8 M, 10 -6 The solution of M was prepared, and then the prepared Rhodamine 6G aqueous solution was dropped onto the prepared substrate. After the Rhodamine 6G aqueous solution evaporated, Raman spectroscopy was performed using a laser wavelength of 532 nm. The results are as follows. Figure 6 As shown, it can be seen that even when the concentration of Rhodamine 6G in the aqueous solution is as low as 10... -14 M can still be detected, indicating that the prepared substrate has high sensitivity.
[0102] The present invention has been described in detail above with reference to preferred embodiments and exemplary examples. However, it should be noted that these specific embodiments are merely illustrative explanations of the invention and do not constitute any limitation on the scope of protection of the invention. Various improvements, equivalent substitutions, or modifications can be made to the technical content and embodiments of the present invention without departing from the spirit and scope of protection of the invention, and all such modifications fall within the scope of protection of the present invention. The scope of protection of the present invention is defined by the appended claims.
Claims
1. A method for preparing a flexible surface-enhanced Raman spectroscopy substrate, characterized in that, The method includes: Step 1: Deposit a metal with a thickness of 2~10nm on the surface of the substrate (5) in one step. Heat treat the substrate (5) after one deposition at 150~250℃ for 0.5~3h to cause the metal to undergo a dewetting effect and form an isolated metal nanostructure layer (1) on the surface of the substrate (5). The substrate (5) with the metal nanostructure layer (1) is placed in a self-assembled molecular solution for 4-8 hours. By utilizing the chemical bonds between the self-assembled monomolecule and the metal, a self-assembled monolayer (2) is formed only on the surface of the metal nanostructure layer (1). The self-assembled molecular solution is an octadecyl mercaptan-isopropanol solution or an octadecyl mercaptan-ethanol solution. Step 2: A metal layer (4) with a thickness of 10~60nm is deposited a second time on the surface of the substrate (5) with the self-assembled monolayer (2). The self-assembled monolayer (2) is located between the metal nanostructure layer (1) and the metal layer (4), forming a metal nano gap (21) with a width of 3~5nm between the metal layer (4) and the metal nanostructure layer (1) below. The width of the metal nano gap (21) is equal to the molecular chain length of the self-assembled monolayer. Step 3: Apply flexible organic material to the metal layer (4) at 50~120°C. o After curing at C for 30-120 minutes, the flexible organic material with deposited metal layer (4) and self-assembled monolayer (2) is peeled off from the substrate (5) to obtain the substrate. In the above steps, the metal is gold or silver.
2. The method according to claim 1, characterized in that, The metal nano gaps (21) are arranged in an array on the substrate surface.
3. The method according to claim 1, characterized in that, The substrate is based on a flexible organic material (3), and a metal layer (4) is attached to the surface of the substrate (3).
4. The method according to claim 3, characterized in that, The metal layer (4) includes an array of metal nanostructure layers (1), which are separated from the metal layer (4) by a self-assembled monolayer (2).
5. The method according to claim 1, characterized in that, In step 1, the substrate (5) is a silicon wafer or quartz glass.
6. The method according to claim 3, characterized in that, The flexible organic material is a polymer or organosilicon.
7. The application of the substrate prepared by the method according to any one of claims 1 to 6 in Raman spectroscopy detection.
Citation Information
Patent Citations
Metal nano hemispherical shell array SERS detection transparent flexible substrate and preparation method thereof
CN112179886A
Raman-active nanoparticle for surface-enhanced raman scattering and method of producing the same
US20220349826A1